This Land Is Our Land The Struggle for a New Commonwealth. - Purdy, Jedediah (Princeton University Press, 2021)
From one of our finest writers and leading environmental thinkers, a powerful book about how the land we share divides us--and how it could unite usToday, we are at a turning point as we face ecological and political crises that are rooted in conflicts over the land itself. But these problems can be solved if we draw on elements of our tradition that move us toward a new commonwealth--a community founded on the well-being of all people and the natural world. In this brief, powerful, timely, and hopeful book, Jedediah Purdy explores how we might begin to heal our fractured and contentious relationship with the land and with each other.
Description based upon print version of record.
Keywords: Land use -- Social aspects -- United States.; Land use -- Environmental aspects -- United States.; United States -- Politics and government.; United States -- Environmental conditions.; Utilisation du sol -- Aspect social -- États-Unis.; Utilisation du sol -- Aspect de l'environnement -- États-Unis.; États-Unis -- Politique et gouvernement.; POLITICAL SCIENCE / Public Policy / Environmental Policy; Ecology; Land use -- Environmental aspects; Land use -- Social aspects; Politics and government; United States; Accounting.; Activism.; American exceptionalism.; Americans.; Ammon Bundy.; Barbarian.; Bernie Sanders.; By-product.; Capitalism.; Civil disobedience.; Clean Water Act.; Climate change.; Coal mining.; Coal.; Colonization.; Denialism.; Die-in.; Disaster.; Disenchantment.; Disgust.; Dissident.; Drinking water.; Duke University.; Ecological crisis.; Employment.; Energy development.; Engineering.; Environmental Defense Fund.; Environmental issue.; Environmental justice.; Environmental law.; Environmental movement.; Environmental politics.; Environmental stewardship.; Environmentalism.; Environmentalist.; Exhaustion.; Exit poll.; Exoskeleton.; Faculty of Law.; Fuel.; Future generation.; Gilded Age.; Global catastrophic risk.; Green New Deal.; Harvard University.; Henry David Thoreau.; Household.; Human power.; Indigenous peoples.; Infrastructure.; Institution.; Interdependence.; Labour movement.; Lecture.; Legislation.; Legislator.; Martin Luther King, Jr.; Meriwether Lewis.; Military occupation.; Mining.; Moral Mondays.; Narrative.; Natural disaster.; Our Choice.; Overburden.; Pasture.; Pauli Murray.; Politics.; Pollutant.; Pollution.; Princeton University Press.; Priscilla Wald.; Proclamation.; Racism.; Romanticism.; Ruler.; Sanctuary movement.; Sasson.; Slavery.; Soil.; Sorkin.; Sovereignty.; Statute.; Surface runoff.; Symptom.; Ta-Nehisi Coates.